Comment on: Tang et al. [2019]: A problematic animal fossil from the early Cambrian Hetang Formation, South China. (November 2019) - Slater, Ben J.; Budd, Graham E.
Abstract: Tang et al. (2019) described new specimens of carbonaceous compression fossils from the early Cambrian Hetang Formation in South China, for which they established the new taxon Cambrowania ovata Tang and Xiao in Tang et al., 2019. Tang et al. (2019) interpreted these fossils as the remains of metazoans, representing either the carapaces of bivalve arthropods, or early life-cycle stages of sponges. We contest the animal affinity of these fossils; instead, we propose that the specimens described as Cambrowania ovata are actually large Leiosphaeridia —in other words, collapsed hollow organic spheroidal acritarchs. The features described by Tang et al. (2019) all fall into the morphology of carbonaceous compressions of Leiosphaeridia with pyritized/baritized folds and compaction wrinkles. Such Leiosphaeridia are a common component of Cambrian (and older) siliciclastic deposits, and frequently exhibit such a pattern of pyritization, baritization, and encrustation with other diagenetic minerals.